Regulatory distortion of management compensation: The case of golden parachutes for bank managers - Evans, Jocelyn; Noe, Thomas H.; Thornton, John H. (Journal of Banking & Finance, 1997)
This paper examines whether golden parachute adoptions in the banking industry during the eighties aligned the interests of CEOs with those of regulators and or shareholders. Our results provide evidence supporting concerns expressed by regulators: that boards of directors behaved opportunistically by adopting golden parachutes prior to large bank failures in order to exploit the FDIC guarantee. Parachute adoption was correlated with poor performance ex ante and ex post. Moreover, adoption of parachutes virtually ceased when the FDIC guarantee was withdrawn by FDICIA.